Analisa Logo Uma Art Space melalui Pendekatan Teori Semiotika Roland Barthes - Hasian, Irene; Fajri, Akbar Kukuh (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Media Komunikasi Trisakti, 2018)
The development of the world very rapidly, it can be seen from the technology, at this time we are very easy to access the internet, and get stuff we want, even not only from the side of technology that can be considered, from the side of creativity we can certainly see also rapid development. UMA Art Space is a company that became a receptacle engaged in art and creativity, particularly painting devoted to self-improvement of young artists in Indonesia, through the works. Myth or mite is part of semiotics Roland Barthes, the myth is a thing that can be believed but could not be proved. In the process of preparing a qualitative descriptive method using writing outlining the results of the research on logo Uma Art Space, which proves the meaning, and the values contained in the logo, using the approach to the theory of semiotics Roland Barthes. The results of the analysis in the logo Uma Art Space, the logo is owned by Uma Art Space already has criteria as a good logo, representing the company’s vision and mission, and has a meaning that is directly related to the company or the owner of the company.